1991
DOI: 10.1007/bf01309021
|View full text |Cite
|
Sign up to set email alerts
|

Iodine in mineral waters: A comparison of results from two analytical techniques

Abstract: Abstract.A comparative study of the determination of iodine in mineral waters is presented. Iodine was first determined by a standard titrimetric method and the results obtained were compared with those obtained by the faster and more sensitive radiochemical neutron activation method. For a series of waters, the results obtained by the two techniques were in fair agreement for the higher concentration levels of iodine, but for very low iodine levels the titrimetric method was insufficiently sensitive. The RNAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It has been reported that neutron irradiation of aqueous samples with iodine in polyethylene vials resulted in a significant loss of activity of iodine on the walls (up to 60−70% of total iodine), which can be avoided by addition of ammonia or ethanol, but a reverse result has also been reported for the analysis of organic bound iodine and mineral water . Thus, we tested the adsorption of iodine in deionized water and seawater on the wall of a polyethylene vial during neutron irradiation by measuring the iodine content on the polyethylene vial after irradiation.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…It has been reported that neutron irradiation of aqueous samples with iodine in polyethylene vials resulted in a significant loss of activity of iodine on the walls (up to 60−70% of total iodine), which can be avoided by addition of ammonia or ethanol, but a reverse result has also been reported for the analysis of organic bound iodine and mineral water . Thus, we tested the adsorption of iodine in deionized water and seawater on the wall of a polyethylene vial during neutron irradiation by measuring the iodine content on the polyethylene vial after irradiation.…”
Section: Resultsmentioning
confidence: 98%
“…In seawater, the concentrations of sodium, chlorine, and bromine are quite high, and it is difficult to directly determine iodine by instrumental NAA. Thus, ion-exchange preconcentration 30 and postirradiation radiochemical NAA 32 (RNAA) have been used for the determination of iodine in seawater. In this work, the postirradiation NAA was chosen for the determination of iodine content in natural seawater and the different separated fractions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, few papers describing detailed studies of iodine stability in the preparation and analysis process are available. Belling et al 5,6 studied the recovery of iodine in dry, alkali ash and acid digestion, Zaichick and Zaichick 7 and Ishikawa et al 8 studied the loss of iodine in lyophilisation of biological samples and Heurtebise and Ross 9 and Byrne et al 10,11 investigated the loss of iodine in neutron irradiation. However, in all these papers, the analyte investigated was total iodine in the samples, and no study of the stability of different chemical species of iodine in the sample preparation process was reported.…”
mentioning
confidence: 99%